The Role of Financial Technologies in Ensuring the Sustainable Development of Agricultural Businesses - MASLAK, Nataliia; ABBASOV, Rasim Cavan; BRATUS, Hanna; PYRTKO, Mykhaіlo; SYMONENKO, Olena (Theoretical and Practical Research in Economic Fields; Vol 16 No 2 (2025): TPREF, Volume XVI, Issue 2(34), Summer 2025DO - 10.14505/tpref.v16.2(34).06, 2025)
The role of financial technologies (FinTech) in ensuring the sustainable development of agricultural businesses is gradually becoming relevant for the agricultural sector, especially in view of the problems and obstacles facing small and medium-sized agricultural companies. The aim of the study is to assess the impact of the use of FinTech on the sustainable development of the agricultural sector. A structured online questionnaire with ten questions was developed to collect data covering the level of implementation, usage frequency, and the impact of FinTech on the sustainable development of agricultural businesses. Quantitative correlation analysis was used to assess the statistical relationship between the FinTech usage rate and sustainable development indicators. The analysis of variance (ANOVA) determined the strength and direction of the impact of FinTech on the economic, social, and environmental aspects of sustainable development. The study showed that the active use of financial technologies among agricultural companies remains limited. Mobile payments, online banking, and automation of financial processes are the most common financial instruments. It was found that insufficient awareness of companies, financial barriers, and technical difficulties hinder the active implementation of financial technologies. For the first time, an assessment of the level of implementation of FinTech in the agricultural sector of Poltava region was carried out and the main tools used by agricultural companies were identified. Further research may focus on studying the impact of individual FinTech innovations on the productivity of agricultural businesses.